Konsep Dasar Supervisi dalam Pendidikan - Syifa Aulia Assabilla; Nabilah Afifah; Subandi Subandi (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
Supervision in the world of education has a very important role to improve the quality of teaching and learning. The supervision process aims to provide guidance, evaluation and support to teaching staff so that they can achieve the educational goals that have been set. This article reviews the basic concepts of supervision in the educational context, identifying the objectives, functions, principles and methods used in implementing educational supervision. It is hoped that this understanding of supervision can provide deeper insight into how to improve the quality of education through an effective supervision process.